V for vendetta - Moore, Alan 1953-; Lloyd, David 1950-.; Whitaker, Steve; Dodds, Siobhan (New York DC Comics, 1989)
Rebellion brews in a fictitious 1990's post-war London.
Europe after the reign -- This vicious cabaret -- The land of do-as-you-please -- Behind the painted smile -- Vertigo -- Vincent.
"Originally published in magazine form in the United States as V for Vendetta #1-10"--T.p. verso.
UCWS-3379g donated by Carljoe Javier - September 2017
Keywords: Totalitarianism -- Comic books, strips, etc; Graphic novels